Sources, topics and use of knowledge by coaches - Stoszkowski, J.; Collins, D. (Journal of Sports Sciences, 2016)
In recent years, the value of social learning approaches as part of the design and delivery of formalised coach development initiatives has gained credence in the literature. However, insight is currently lacking into the fundamental social dimensions that underpin coach learning. Accordingly, this study aimed to explore coaches` perceptions of their actual and preferred methods of acquiring new coaching knowledge, the types of knowledge they currently acquire and/or desire, and their application of new knowledge. Responses to an online survey, completed by practicing coaches (N = 320) in a range of sports and contexts, were analysed descriptively and inductively. Results revealed that coaches preferred, and mostly acquired, coaching knowledge from informal learning activities, especially when these permitted social interaction. Notably, however, formal coach education courses were also reported relatively frequently as a source of recent knowledge acquisition. Nevertheless, critical justification for and application of acquired knowledge was largely absent. Based on the findings, we suggest that, before social learning activities such as mentoring schemes and communities of practice are placed at the centre of formalised coach development provision, coach educators must put in place the support structures to better enable coaches to recognise and deal with the potentially mixed influences of the social milieu on coach learning, aiming to ensure that their informal development is sufficiently open-minded, reflective and critical.